Kontekstualisasi Experiential Learning Theory David Kolb pada Pembelajaran Pendidikan Agama Hindu - Rudiarta, I Wayan; Adnyana, Putu Budi; Ariawan, I Putu Wisna; Wesnawa, I Gede Astra (Jawa Dwipa, 2025)
Learning is an activity that is an important part of the Education. Experiential learning is one of the learning options that can be given to students that allows student involvement to be greater. One of the learning models that seeks to accommodate experience as an essential part is Experiential Learning Theory which encourages students to think more, explore, question, make decisions, and apply something learned. This research aims to conduct a critical analysis related to David A. Kolb's ideas in the context of learning Hindu Religious Education in the school environment. Qualitative research methods with the literature review paradigm are an option in conducting research with a philosophical hermeneutic approach. Research data was obtained through book reviews, scientific articles, and other relevant scientific writings. Data analysis follows the steps outlined by Miles and Huberman, namely data collection, data reduction, data presentation, and presentation of results. The results of the study show that the Experiential Learning Kolb model contextualized with Hindu Religious Education learning will provide convenience for teachers in achieving the formulation of learning outcomes, especially in the material aspects of Sradha and Bhakti, Susila, and Events. By following the cycle structure of Concrete Experience, Reflection Observation, Abstract Conceptualization, and Active Experimentation, teachers can determine the right learning steps for all dimensions of knowledge, ranging from factual, metacognitive, conceptual to procedural. Through this model, the Deep Learning approach can also be implemented to provide a more meaningful, conscious and fun learning experience for students.